T‐Hex: Tilted hexagonal grids for rapid 3D imaging. Issue 5 (3rd December 2020) - Engel, Maria; Kasper, Lars; Wilm, Bertram; Dietrich, Benjamin; Vionnet, Laetitia; Hennel, Franciszek; Reber, Jonas; Pruessmann, Klaas P.
Abstract : Purpose: The purpose of this work is to devise and demonstrate an encoding strategy for 3D MRI that reconciles high speed with flexible segmentation, uniform k‐space density, and benign T 2 ∗ effects. Methods: Fast sampling of a 3D k‐space is typically accomplished by 2D readouts per shot using EPI trains or spiral readouts. Tilted hexagonal (T‐Hex) sampling is a way of acquiring more k‐space volume per excitation while maintaining uniform sampling density and a smooth T 2 ∗ filter. The k‐space volume covered per shot is controlled by the tilting angle. Image reconstruction is performed with a 3D extension of the iterative SENSE approach, incorporating actual field dynamics and static off‐resonance. T‐Hex imaging is compared with established 3D schemes in terms of speed and noise performance. Results: Tilted hexagonal acquisition is found to achieve greater imaging speed than known alternatives, particularly in combination with spiral trajectories. The interplay of the proposed 3D trajectories, array detection, and off‐resonance is successfully addressed by iterative inversion of the full signal model. Enhanced coverage per shot is of greatest utility for high speed in an intermediate resolution regime of 1 to 4 mm. T‐Hex EPI combines the benefits of extended coverage per shot with increased robustness against off‐resonance effects. Conclusion: Sampling of tilted hexagonal grids is a feasible means of gaining 3D imaging speed with near‐optimal SNR efficiency and benign depiction properties. It is a particularly promising technique for time‐resolved applications such as fMRI.